The mediating role of employee commitment on the impact of human resource management practices and transformational leadership style on employee performance - Mahfouz, Shatha Suleiman Atieh Abu; Universiti Sultan Zainal Abidin . Faculty of Business and Management (2021)
Improving the performance of the employees in the construction sectors in Jordan is
extremely important since the industry contributes significantly to the country's
economy. Every year, huge development fund is spent on the industry since it triggers
other economic activities. However, the sector itself is still confronted with issues
concerning lack of qualified workforce, human resource practices, leadership,
employee commitment, and employee performance that slow down economic growth.
As a result, many projects are being suspended and there are even occurrences of
work closure. Consequently, the research was aimed at investigating the mediating
effect of employee commitment on the impact of HRM practices and transformational
leadership style on employee performance of building construction companies in
Jordan. A survey research design that incorporated quantitative method and cross
sectional study of the employees of construction companies was employed to test the
hypothesised relationship among the constructs. The sampling frame of the target
population was not available and staff directory was not available. Hence, the
researcher had to develop a surrogate sampling frame by distributing self-administered
questionnaires to the respondents and draw a random sample from the surrogate
sampling frame. Consequently, 1000 usable questionnaires were returned to be used
as surrogate sampling frame. Using simple random sampling method, a total of 300
respondents were selected randomly. Data were analysed using Structural Equation
Modelling (SEM) technique through lBM-SPSS-AMOS version 24.0 software. HRM
practices were found to have a significant effect on employee performance and
employee commitment. Transformational leadership had significant indirect irnpact on
employee performance. Employee commitment had significant direct Impact on
employee performance. Employee ommitment acted as a partial mediator of the
relationship between HRM practices and employee performance. Employee
commitment also fully mediated the relationship between transformational leadership
and employee performance. The novelty of the research was the construction of an
inductive model, called the Employee-Directed Transformational Leadership Model
(EDTLM), which theoretically implied relationships among transformational
leadership, human resource practices, employee commitment, and employee
performance. The research had proven that employee commitment was one of the
influencers of employee performance. It partially mediated the relationship between
human resource practice and employee performance and fully mediated the
relationship between transformational leadership and employee performance. The
other influencers were human resource practice and transformational leadership. The
findings could be used to guide the management team of building construction
companies in Jordan to focus on the interrelationships among EDTLM constructs,
their variables, and values to improve employee performance. The government and
policy makers alike should utilize the research outcomes to spur the economic
development of the country.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Analysis and findings -- 5. Discussion and conclusion
Thesis (Degree of Doctor of Philosophy) - Universiti Sultan Zainal Abidin, 2021
Includes bibliographical references (leaves 289-325)
Keywords: Universiti Sultan Zainal Abidin -- Faculty of Business and Management -- Dissertations; Universiti Sultan Zainal Abidin -- Dissertations; Communication in management; Dissertations, Academic; Employee motivation; Personnel management